Pengaruh Model Pembelajaran Numbered Head Together Kolaborasi dengan Course Review Horay Terhadap Hasil Belajar - Munazah, Nur; Rahmad; Sulistyowati (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
Determining student learning results and enhancing learning outcomes following the use of the NHT and CRH learning models are the goals of the research. This kind of research uses a quantitative, pre-experimental methodology. Purposive sampling was utilized in the sample collection technique, with all class IV students at MIS Miftahul Huda 2 Palangka Raya serving as research subjects. Learning outcomes are instruments. In the classroom environment, learning results are significantly higher when the NHT CRH collaborative model is used. The Paired Sample T-test, which indicates a significant difference (sign < 0.05) between the pretest and posttest scores, supports this. These findings suggest that when the NHT and CRH models are combined, learning outcomes improve.